La question du genre. Entretien avec Joan W. Scott - Joan W. Scott; Bruno Perreau (Genre, Sexualité et Société)
In this interview conducted by Bruno Perreau, Joan Scott, a professor of history at the Institute for Advanced Study at Princeton, analyzes the emergence of gender studies in France and the United-States. Looking back on her own career, she questions the methods of historical analysis and sheds a new light on the public debate of the veil. Joan Scott sets aside the habitual culturalist arguments and emphasizes the complexity of power relations within feminist movements in a postcolonial context.